Bis(μ-4-nitrophthalato)bis[diaqua(1,10-phenanthroline)manganese(II)] - Xu, Bi-Yi (International Union of Crystallography, 2009)
In the title compound, [Mn(2)(C(8)H(3)NO(6))(2)(C(12)H(8)N(2))(2)(H(2)O)(4)], the Mn(II) atom in the centrosymmetric binuclear unit has a distorted octahedral geometry and is coordinated by a chelating 1,10-phenanthroline ligand, two monodentate carboxylate anions from two 4-nitrophthalates and two coordinated water molecules. The two Mn(II) ions in the molecule are bridged by two 4-nitrophthalate anions, both in a bis-monodentate mode, which finally leads to the formation of the binuclear unit. Intramolecular O—H⋯O hydrogen bonds between the coordinated and uncoordinated O atoms of one monodentate carboxylate group and the corresponding coordinated water molecules result in an eight-membered and two six-membered rings. In the crystal structure, intermolecular O—H⋯O hydrogen bonds link the dinuclear molecules into supramolecular chains propagating parallel to [100].